Variation of trace and radioactive element in the Hatıldag oil shale (HOS): Factors controlling of depositional environment, Göynük Area, Bolu, Turkey. (September 2016) - Koç, Şükrü; Sari, Ali; Yavuz Pehlivanli, Berna
Highlights: In this study a total of 26 samples were examined. The major and trace elements of the samples were analyzed with ICP-ES and with ICP-MS methods. Total organic carbon (TOC) analysis and The gamma-ray spectrometry analysis on kerogen samples were examined. The Hatıldağ oil shales were formed in a shallow marine environment are represented by high organic material content but relatively lower radioactive element enrichment reflecting special deposition conditions to be investigated. Abstract: In this study trace element and radioactive element contents of the Hatıldağ oil shale (HOS) in Turkey and geochemical processes controlling the deposition of these elements are investigated. Ratios of redox-sensitive elements show that HOS were formed in mostly dioxic-anoxic and partly euxinic conditions. Element contents of shales in the northern part are associated mostly with clays and slightly with organic material. It was determined that uranium in southern part is derived from phosphates and calcium-carbonates and thorium is mostly originated from organic material and slightly associated with phosphate and calcium-carbonate. Radioactivity of HOS is derived from uranium and potassium.